Variables associated with subclinical atherosclerosis in a cohort of rheumatoid arthritis patients: Sex-specific associations and differential effects of disease activity and age. - Delia Taverner; Joan-Carles Vallvé; Raimón Ferré; Silvia Paredes; Lluís Masana; Antoni Castro (PLoS ONE, 2018)
To advance the study of variables associated with subclinical atherosclerosis in rheumatoid arthritis (RA) with special consideration for the degree of disease activity, age and gender.The carotid intima-media thickness (cIMT) and the presence of carotid atherosclerotic plaques along with clinical and biochemical characteristics were determined in 214 RA patients.Adjusted analysis reveals that men had a 0.059 mm significantly increased cIMT compared with women (p = 0.001; R2 = 3.8%) and that age was associated with cIMT (β = 0.0048 mm; p = 0.0001; R2 = 16%). Interestingly, we observed a significant interaction between gender and age. Thus, the effect of age on cIMT was significantly increased (12%) in men compared with women (p-value for interaction term = 0.041). Moreover, adjusted multivariable linear regression analysis revealed that disease activity score (DAS28) was significantly associated with cIMT in women (β = 0.021; p = 0.018: R2 = 0.03) but not men. In particular, women with high disease activity had a 0.079 mm increased cIMT compared with women in remission (p = 0.026). In addition, men in remission had a 0.134 mm increased cIMT compared with women in remission (p = 0.003; R2 = 8.7%). Active patients did not exhibit differences in cIMT values. Furthermore, 43% of patients presented carotid plaques. The variables independently associated with carotid plaques were age, smoking, health assessment questionnaire, erythrocyte sedimentation rate and rheumatoid factor (p<0.0001; R2 = 46%).In our cohort of patients with RA, DAS28 and age are differentially associated with cIMT in men and women. Our findings could explain the contradictory results that have previously been published in the literature.